Physical Fitness Profile Of Female : Volleyball Athletes In BVB Club (Bina Voli Banyumas) - Amri Ikhsanul Amal Amri (Universitas Negeri Surabaya, 2025)
Background: A volleyball player needs to be in good shape since it will help them improve their tactics, techniques, and mental state.Objectives: The aim of this study was to find out how fit the female volleyball players of the BVB (Bina Voli Banyumas) club were.Methods: This type of research is quantitative with a descriptive approach. The sample in this study used a total sampling technique, namely all 11 female athletes of the BVB (Bina Voli Banyumas) club. The research instrument uses physical condition test components which include: speed, agility, strength, coordination, explosive power and endurance.Results: The speed component as many as 11 athletes are classified in the good category with a percentage of 100%, the agility component as many as 11 athletes are classified in the very poor category with a percentage of 100%, the strength component as many as 3 athletes are classified in the good category with a percentage of 27% and as many as 8 athletes are classified in the very good category with a percentage of 73%, the explosive power component as many as 4 athletes are classified in the good category with a percentage of 36%, as many as 6 athletes are classified in the fair category with a percentage of 60% and as many as 1 athlete is classified in the less category with a percentage of 4%, the coordination component as many as 4 athletes are classified in the good category with a percentage of 37%, as many as 2 athletes are classified in the fair category with a percentage of 18%, as many as 3 athletes are classified in the poor category with a percentage of 27% and as many as 2 athletes are classified in the very poor category with a percentage of 18%, the endurance component as many as 5 athletes are classified in the poor category with a percentage of 46%, as many as 4 athletes are classified in the poor category with a percentage of 36% and as many as 2 athletes are classified in the very poor category with a percentage of 18%.Conclusion: The physical fitness profile of female volleyball athletes at the BVB (Bina Voli Banyumas) club ranges from poor to very good. The category that needs improvement is agility.